1984
DOI: 10.4188/jte1955.30.35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scouring and Bleaching on the Abrasion Life of Sized Yarns

Abstract: With a modified Hiruta's abrasion tester, were studied the abrasion life and the elongation of sized yarns, scoured and bleached in a state of soft cheese before sizing.It was found that averages of these measured values had relation to the shrinkage rate of scouredbleached yarns in 30° Be NaOH solution, but no relation to the whiteness of yarns.On the other hand, the probability of abrasion life indicated a broken line on a Weibull probability paper showing the catastrophic distribution for specimens having l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Materials, methods of preparation, results of weaving tests, and fabric properties of samples [1][2][3][4][5][6][7][8][9][10][11][12] are described in reference 6. Sampie 13 was prepared in the same way as sample 12, and samples 14-16 were sized with polyvinyl alcohol ( PVA ) in a Callaway slasher ( 7 ] .…”
Section: Experimental Materials and Weaving Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Materials, methods of preparation, results of weaving tests, and fabric properties of samples [1][2][3][4][5][6][7][8][9][10][11][12] are described in reference 6. Sampie 13 was prepared in the same way as sample 12, and samples 14-16 were sized with polyvinyl alcohol ( PVA ) in a Callaway slasher ( 7 ] .…”
Section: Experimental Materials and Weaving Performancementioning
confidence: 99%
“…Zweigle abrasion tester [ 5 ], the Vezelinstitut TNO abrasion tester [I ], the Reutlinger Webtester [ 12 ] , TRI's cyclic tensile abraders ( CTA ) [ 2,3,11 ] , and the Hitata abrasion tester [ 9 ] . Several studies have reported that no consistent correlations can be found between abrasion resistance and weaving performance [ 10 ] , however, and reproducibility of abrasion testing results from laboratory to laboratory and machine to machine has been very poor.…”
mentioning
confidence: 99%